Nilai konsumen dalam "Aku tahu apa yang aku beli" - Wangsa, Ignasius Heri Satrya (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2021)
The consumer can make the best decision based on his natural capacity as a rational and economic man. Practically, this rationality is determined by new values accumulated from previous consumption experience. This research aims at studying consumers' values through rationalization of relevant variables in consumers values mix. Context of consumer confidence "I know what to buy" represents his independence as a consumer who treasures assurance and certainty reflected upon specific values. Consumers subscribe to these values as the primary reference in consumer buying behavior. Additionally, this context facilitates the study on consumer value resistance about the internal and external environment pressure. This research contributes to consumer's values theory through a mixed-method.